Influence of Body Size on Fecundity and Egg Diameter and Their Correlations in Female Freshwater Lobsters (Cherax quadricarinatus) - Nadya Almira Pustpitadewi; Prayogo; Nguyễn Ngọc Quyến; Darmawan Setia Budi Budi (Airlangga University, 2025)
Broodstock size is crucial for determining reproductive success in freshwater lobsters (Cherax quadricarinatus), influencing fecundity and egg diameter. This study aims to analyze the effects of broodstock size on fecundity and egg diameter and their correlations to optimize hatchery management. Thirty egg-bearing female C. quadricarinatus were categorized into three size groups: small (10.5–12.5 cm), medium (12.6–14.5 cm), and large (14.6–16.5 cm). Fecundity and egg diameter were analyzed using one-way ANOVA and regression analysis. The results showed that larger females produced a significantly higher number of eggs (p < 0.05), while smaller females had larger egg diameters. Regression analysis revealed a positive correlation between body size and fecundity but a negative correlation with egg diameter. This study concluded that, among the tested size groups, medium-sized broodstock (12.6–14.5 cm) exhibited the most optimal balance between fecundity and egg size, making it the preferred choice for hatchery management. These findings provide valuable insights for improving broodstock selection and enhancing seed production efficiency in C. quadricarinatus aquaculture